The answer, for what its worth, is 495397431375829912
Chat with our AI personalities
4 x 4 x 4 x 4 x 4 = 45
(-9x^2/√x) + 4= [-9x^2/x^(1/2)] + 4= (-9x^2)[x^(-1/2)] + 4= -9x^[2 + (-1/2)] + 4= -9x^(2 - 1/2) + 4= -9x^(3/2) + 4= -9√x^3 + 4= -9√[(x^2)(x)] + 4= -9x√x + 4Or,(-9x^2/√x) + 4= [(-9x^2)(√x)/(√x)(√x)] + 4= [(-9x^2)(√x)/√x^2] + 4= [-9(x)(x)(√x)/x] + 4 simplify x= -9x√x + 4
x2 - 3x - 4 = 0 so (x+1)(x-4) = 0, so x+1 = 0 and x-4 = 0, so x = -1 or 4
(X-5)(X+4)=0 so X-5=0 -----X=5 and X=4=0 so X=-4 it factors to (X-5)(X+4) so X=5,-4
(x+4)(x+4), or (x+4)^2.